A reunification of the US (“NIH”) and International Unit into a single standard for Thrombin - Whitton, Colin; Sands, Dawn; Lee, Timothy; Chang, Andrew; Longstaff, Colin (Thrombosis and Haemostasis, 2005)
The existence of two different units forThrombin in widespread international use has caused confusion for many years. The holders of the WHO International Standard (IS) for Alpha Thrombin and the US Standard (also known as the “NIH Standard”) now report on a collaboration to reunite the International Unit (IU) and the US unit (“NIH unit”).A study was organised involving 25 laboratories in 15 countries to investigate the possibility of preparing a common Standard with a common unit and to investigate aspects of methodology that cause divergence of results using the IS and US Standard. Laboratories were asked to measure the potency of two candidate replacement standards (C, 01/578 and D, 01/580), and potencies were calculated relative to both the existing US Standard (lot J) and the IS (89/588). Data analysis of a total of 128 assays indicated that sample D would make an ideal replacement joint Standard with a potency of 110 IU/ampoule (equivalent to 110 US units per ampoule) based on data from clotting assays. No significant differences in results were observed using fibrinogen of human or bovine origin, or using human plasma. Comparisons of chromogenic and clotting assays indicated that sample D had a similar high proportion of alpha thrombin to the current IS for Alpha Thrombin (89/588). Sample D was adopted as the IS for Thrombin (01/580) and the US Standard (lot K) with a potency of 110 IU/ampoule.
Keywords: Thrombin standardization; clotting assays